With these, always write out the multiples first.
Start like this:
(assume one of the factors is negative)
1 and 1120
2 and 560
4 and 280
5 and 224
7 and 160
8 and 140
10 and 112
14 and 80
16 and 70
20 and 56
28 and 40
32 and 35
from those, the obvious choice is the one with a difference of three. In this case, 32 and 35, because -32 + 35 equals 3.
Answer:
37.57
Step-by-step explanation:
34 + 15.45 - 19.75 + 7.87
34 + 15.45 = 49.45
49.45 - 19.75 + 7.87
49.45 + 7.87 = 57.32
57.32 - 19.75 = 37.57
Proving a relation for all natural numbers involves proving it for n = 1 and showing that it holds for n + 1 if it is assumed that it is true for any n.
The relation 2+4+6+...+2n = n^2+n has to be proved.
If n = 1, the right hand side is equal to 2*1 = 2 and the left hand side is equal to 1^1 + 1 = 1 + 1 = 2
Assume that the relation holds for any value of n.
2 + 4 + 6 + ... + 2n + 2(n+1) = n^2 + n + 2(n + 1)
= n^2 + n + 2n + 2
= n^2 + 2n + 1 + n + 1
= (n + 1)^2 + (n + 1)
This shows that the given relation is true for n = 1 and if it is assumed to be true for n it is also true for n + 1.
<span>By mathematical induction the relation is true for any value of n.</span>
Answer:
10
Step-by-step explanation:
The hypotenuse of a triangle is the side that is opposite to the right angle, meaning that none of its endpoints form the right angle. In this case, the hypotenuse is LN which is 10.
Answer:
1+cos^2(2A)=(1−cos2(2A))+2cos^2(2A)
=sin^2(2A)+2(cos^2A−sin^2A)^2
=(2sinAcosA)^2+2(cos^4A−2cos^2Asin^2A+sin^4A)
=2(cos^4A+sin^4A)
Step-by-step explanation: